Wound Healing Splinting Devices for Faster Access and Use - Andrew W. Miller; Alexa R. Anderson; Alejandra Suarez-Arnedo; Tatiana Segura (JID Innovations)
With the goal of studying skin wound healing and testing new drug treatments to enhance wound healing in rodent models, there is a clear need for improved splinting techniques to increase surgical efficiency and support routine wound monitoring. Splinted wound healing models humanize wound healing in rodents to prevent contraction and instead heal through granulation tissue deposition, increasing the relevance to human wound healing. Current technologies require suturing and heavy wrapping, leading to splint failure and cumbersome monitoring of the wound. In this study, we developed a splint with resealable cap system that provides ease of access for wound inspection, therapeutic treatment delivery, and routine wound imaging without the need to unwrap and wrap the animal. Meanwhile, to overcome the challenges associated with suturing, we also developed adherent splints that can be applied to both hairless or haired mice with minimal wrapping. Both technologies are expected to improve and encourage the adoption of splinted wound healing models.